La Vigencia de Sor Juana Inés de la Cruz - Pérez Martínez, Herón (Acta Universitaria, 2008)
More than three hundred and twelve years have passed since the death of Sor Juana Inés de la Cruz, and we do not have a trustworthy biography of the poet or even a complete study of her poetic works, which, as is now known, were forged in the intense circumstances of her life. Impeding the fi rst of these are the still unexposed “dark spots” and the yet unresolved “mysteries” that surround her life, according to some scholars. And yet, the wealth of publications during the twentieth century and up to the present time show us a Sor Juana very much alive and present in Hispanic academic life. This article presents an analysis of studies conducted on Sor Juana Inés de la Cruz that have been conducted in recent years, based both on texts she herself wrote and studies devoted to the poet by other authors.